Rekonstruksi Tata Kelola Pelindungan Pekerja Migran Melalui Reposisi BP2MI - Siti Zahra; Sizil Azzahra Sa’dillah; Festy Nur Fajruroh (Fakultas Hukum Universitas Islam Indonesia, 2025)
The increasing number of Indonesian Migrant Workers demands stronger legal protection for their rights, which in turn requires an institutional framework that is both effective and adaptive. However, the discourse surrounding the dissolution of BP2MI—the technical body responsible for PMI protection—raises concerns regarding the effectiveness of the current institutional governance. This study aims to analyze the dynamics of institutional arrangements in the protection of migrant workers in Indonesia and to formulate an ideal reconstruction of institutional governance for their protection. The research employs a normative-juridical method with a conceptual and statutory approach. Data were collected through literature studies involving relevant regulations, journals, and academic sources. The findings indicate that removing the BP2MI nomenclature could significantly reduce the institutional responsiveness to the needs of migrant workers. Therefore, this study recommends the repositioning of BP2MI as an independent and specialized technical body under the Ministry of PMI Affairs to ensure a more effective, accountable, and sustainable protection system for Indonesian migrant workers.